(untitled) (An Naba, 2020)
This research is based on the poor ability of students to understand Arabic texts and the lack of interest in reading that is owned by students. So, the students have difficulty in understanding Arabic lessons. The problem in this research is "Is the Al-Qiroah method able to improve reading comprehension in Arabic languageand how to increase the use of the Al-Qira’ah method in reading comprehension in Arabic class lessons VII A HafshohDarul Fattah Qur’an Middle School? " while the purpose of this research was to determine the effect of the Al-Qira’ah method on reading comprehension in Arabic class VII A Hafshoh Middle School Qur’an Darul Fattah and to describe the increased use of the Al-Qira’ahmethod in reading comprehension in Arabic class VII A Hafshoh Middle School Qur’an Darul Fattah. The type of research that researchers use is Classroom Action Research (CAR). The subject of this research is class VII AHafshoh Middle School Qur’an Darul Fattah amounting to 27 students. This research was conducted in two cycles and each cycle has four learning meetings. In this research, the average value of the students reading comprehension test in the pretest was 60.72, in the first cycle was 66.60 and in the second cycle was 82.02, with the difference in the increase in the pretest to the first cycle increasing by 5.88 points or equivalent to 9.68%. Meanwhile the first cycle to the second cycle increased by 15.42 points or equivalent to 23.15%. It can be concluded that learning by using the Al-Qiro’ah method can improve reading comprehension in Arabic class VII A Hafshoh students at Darul Fattah Qur’an Middle School.